DETERMINASI VARIASI PRODUK KUALITAS PELAYANAN WORD OF MOUTH DAN LOKASI TERHADAP PENINGKATAN VOLUME PENJUALAN DIMEDIASI LOYALITAS PELANGGAN PADA TOKO OLEH-OLEH KHAS LAMONGAN HJ. FATIMAH: Analisis Metode-Partial -Least Square (PLS) – StructuralLEquation Modeling (SEM) - Aulia Firdaus Surya Putri; Abid Muhtarom; Danu Kusbandono (LP2M Universitas Bina Bangsa, 2023)
The development of foreign food businesses entering Indonesia has caused special foods originating from Indonesia to begin to lose their appeal, especially regional specialties, including the Lamongan Hj Fatimah Souvenir Shop business which sells Lamongan Regency specialties. This study used a quantitative method with a total sample of 300 respondents. This study uses SEM analysis using the Smart PLS application version 3.0 and the test tools used are the outer model, inner model, mediation test and hypothesis testing. The results of the research on the variable product variation (X1), service quality (X2), word of mouth (X3) and location (X4) on the increase in sales volume (Y) are mediated by customer loyalty (Z), namely from the validity test the value of outer loading > 0.7 and the number of AVE > 0.5 is declared valid, in the reliability test the value of composite reliability and corbanch's alpha > 0.7 is declared reliable. In the mediation test, the variables of service quality (X2) and location (X4) are stated to be partial mediation, while the variable product variation (X1) and word of mouth (X3) expressed full mediation. From the results of the hypothesis test the service quality variable (X2) and location (X4) have a positive and significant effect on increasing sales volume (Y), while the product variation variable (X1) and word of mouth (X3) have a negative and not significant effect on increasing sales volume ( Y)